PENGARUH PENAMBAHAN KONSENTRAT DENGAN KADAR PROTEIN KASAR YANG BERBEDA PADA RANSUM BASAL TERHADAP KECERNAAN PROTEIN DAN KECERNAAN SERAT KASAR KAMBING BOERAWA PASCA SAPIH - Sukmawan, Asep; -, Liman; -, Erwanto (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aims to: (1) determine the effect of the addition of concentrates with different levels of crude protein in the basal ration for goats Boerawa past-weaning dry matter and organic digestibility and (2) to the addition of the best concentrates on past-weaning dry matter and organic digestibility Boerawa goats. This research used randomized block design, consisting of four treatments, with repeated five times, they are R0: bassal feeding, R1: bassal feeding + concentrate (Crude Protein 13%), R2: bassal feeding + concentrate (CP 16%), and R3: bassal feeding + concentrate (CP 19%). The results shows a significant effect (P <0.05) additions concentrates on bassal feeding to organic matter digestibility Boerawa goats pasca-weaning, the opposite effect was not significant (P>0.05) protein digestibility and crude fiber.